Fractographic Analysis of the Temperature Influence in the Mode I Fatigue Delamination of Carbon/Epoxy Composites - Patricia Coronado; Jaime A. Viña; Antonio Argüelles; Sara Sánchez (Proceedings, 2018)
The present research shows a fractographic analysis, using a scanning electron microscope (SEM), based in previous experimental tests of the delamination under mode I fatigue loading for two aeronautical quality composite materials at different test temperatures (90, 20 and −60 °C) in order to analyze the matrix and temperature influence (flight conditions). The materials employed are composed of two different epoxy matrixes and the same unidirectional carbon fiber reinforcement. This study suggests a variable behavior depending on the temperature and the type of matrix used.